THE IMPACT OF QUALITY PERCEPTION AND VALUE PERCEPTION TOWARD PURCHASE INTENSITY (SURVEY COFFEE SHOP VISITORS IN PADANG CITY) - Agriqisthi Agriqisthi; Rasidah Nasrah (Fakultas Bisnis, 2020)
The attraction of coffee is its unique taste and historical value, tradition, and life style. The phenomenon of coffee shops can not be separated from the habits or culture coffee drinking in community. This has encouraged business people, especially in Padang City to make coffee cafes a promising commodity for business opportunities. The purpose of this research is to find out; the impact of perceived quality on perceived value, and the effect of perceived value on repurchase intention. This research uses quantitative methods and uses SEM-PLS analysis to test research model. The observation unit in this study is customer Coffee Shops in Padang City as many as 120 respondents. In measuring variables using the Likert scale. The results found that the variable perceived quality significantly impact on perceived value, whereas perceived value significantly e on the repurchase intention.